2016
DOI: 10.1093/intqhc/mzw032
|View full text |Cite
|
Sign up to set email alerts
|

eHealth and quality in health care: implementation time

Abstract: The use of information and communication technologies in health and health care could improve healthcare quality in many ways. Today's evidence base demonstrates the (cost-)effectiveness of online education, self-management support and tele-monitoring in several domains of health and care. While new results gradually provide more evidence for eHealth's impact on quality issues, now is the time to come to grips with implementation issues. Documented drawbacks such as low acceptance, low adoption or low adherenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
79
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(98 citation statements)
references
References 27 publications
4
79
0
3
Order By: Relevance
“…A third of the articles were classified as having average / good quality of reporting while only 5.9% were considered excellent. This was consistent with previous research articles that highlighted the poor quality of information in the print media about health-related matters [46,47]. It has been reported that high quality newspaper articles often flow from a press release, generally from a scientific journal [21].…”
Section: Content Of the Selected Articlessupporting
confidence: 91%
“…A third of the articles were classified as having average / good quality of reporting while only 5.9% were considered excellent. This was consistent with previous research articles that highlighted the poor quality of information in the print media about health-related matters [46,47]. It has been reported that high quality newspaper articles often flow from a press release, generally from a scientific journal [21].…”
Section: Content Of the Selected Articlessupporting
confidence: 91%
“…For these reasons, there have been recent calls for a shift in research focus from program development towards program implementation and evaluation to support evidence‐based scale‐up of e‐mental health programs in healthcare settings (Batterham et al, ; Ossebaard & Van Gemert‐Pijnen, ). Implementation science seeks to address the gap of how to put a new intervention into practice and is defined as “the scientific study of methods to promote the systematic uptake of research findings and other evidence‐based practices … to improve the quality and effectiveness of health services and care” (Eccles et al, , p. 2).…”
Section: Introductionmentioning
confidence: 99%
“…Implementation science seeks to address the gap of how to put a new intervention into practice and is defined as “the scientific study of methods to promote the systematic uptake of research findings and other evidence‐based practices … to improve the quality and effectiveness of health services and care” (Eccles et al, , p. 2). Implementation science is an emerging field of research and is beginning to deliver the approaches needed to address the research‐to‐practice gap (Ossebaard & Van Gemert‐Pijnen, ). Numerous theoretical models and frameworks are now available to guide implementation research, such as the consolidated framework for implementation research (CFIR; Damschroder et al, ), Proctor's framework of implementation outcomes (Proctor et al, ), the promoting action on research implementation (PARIHS) framework (Rycroft‐Malone, ) and the reach, effectiveness, adoption, implementation, and maintenance (RE‐AIM) framework (Glasgow, Vogt, & Boles, ), to name a few.…”
Section: Introductionmentioning
confidence: 99%
“…These will increasingly be applied in prevention, cure and care. [14] Once less fragmented and used at a larger scale, this will enable forms of personalized care in the domestic environment, requiring new professional roles and skills.…”
Section: Resultsmentioning
confidence: 99%